Disruption of Phosphodiesterase 3A Binding to SERCA2 Increases SERCA2 Activity and Reduces Mortality in Mice With Chronic Heart Failure. Issue 16 (6th March 2023) - Skogestad, Jonas; Albert, Ingrid; Hougen, Karina; Lothe, Gustav B.; Lunde, Marianne; Eken, Olav Søvik; Veras, Ioanni; Huynh, Ngoc Trang Thi; Børstad, Mira; Marshall, Serena; Shen, Xin; Louch, William E.; et al.
Abstract : Background: Increasing SERCA2 (sarco[endo]-plasmic reticulum Ca 2+ ATPase 2) activity is suggested to be beneficial in chronic heart failure, but no selective SERCA2-activating drugs are available. PDE3A (phosphodiesterase 3A) is proposed to be present in the SERCA2 interactome and limit SERCA2 activity. Disruption of PDE3A from SERCA2 might thus be a strategy to develop SERCA2 activators. Methods: Confocal microscopy, 2-color direct stochastic optical reconstruction microscopy, proximity ligation assays, immunoprecipitations, peptide arrays, and surface plasmon resonance were used to investigate colocalization between SERCA2 and PDE3A in cardiomyocytes, map the SERCA2/PDE3A interaction sites, and optimize disruptor peptides that release PDE3A from SERCA2. Functional experiments assessing the effect of PDE3A-binding to SERCA2 were performed in cardiomyocytes and HEK293 vesicles. The effect of SERCA2/PDE3A disruption by the disruptor peptide OptF (optimized peptide F) on cardiac mortality and function was evaluated during 20 weeks in 2 consecutive randomized, blinded, and controlled preclinical trials in a total of 148 mice injected with recombinant adeno-associated virus 9 (rAAV9)-OptF, rAAV9-control (Ctrl), or PBS, before undergoing aortic banding (AB) or sham surgery and subsequent phenotyping with serial echocardiography, cardiac magnetic resonance imaging, histology, and functional and molecular assays. Results: PDE3A colocalized with SERCA2 in human nonfailing, human failing, and rodent myocardium. Amino acids 277–402 of PDE3A bound directly to amino acids 169–216 within the actuator domain of SERCA2. Disruption of PDE3A from SERCA2 increased SERCA2 activity in normal and failing cardiomyocytes. SERCA2/PDE3A disruptor peptides increased SERCA2 activity also in the presence of protein kinase A inhibitors and in phospholamban-deficient mice, and had no effect in mice with cardiomyocyte-specific inactivation of SERCA2. Cotransfection of PDE3A reduced SERCA2 activity in HEK293 vesicles. Treatment with rAAV9-OptF reduced cardiac mortality compared with rAAV9-Ctrl (hazard ratio, 0.26 [95% CI, 0.11 to 0.63]) and PBS (hazard ratio, 0.28 [95% CI, 0.09 to 0.90]) 20 weeks after AB. Mice injected with rAAV9-OptF had improved contractility and no difference in cardiac remodeling compared with rAAV9-Ctrl after aortic banding. Conclusions: Our results suggest that PDE3A regulates SERCA2 activity through direct binding, independently of the catalytic activity of PDE3A. Targeting the SERCA2/PDE3A interaction prevented cardiac mortality after AB, most likely by improving cardiac contractility.